Targeting the Gut Microbiota to Improve Dietary Protein Efficacy to Mitigate Sarcopenia - de Marco Castro, Elena; Murphy, Caoileann H.; Roche, Helen M. (Frontiers in Nutrition, 2021)
Sarcopenia is characterised by the presence of diminished skeletal muscle mass and strength. It is relatively common in older adults as ageing is associated with anabolic resistance (a blunted muscle protein synthesis response to dietary protein consumption and resistance exercise). Therefore, interventions to counteract anabolic resistance may benefit sarcopenia prevention and are of utmost importance in the present ageing population. There is growing speculation that the gut microbiota may contribute to sarcopenia, as ageing is also associated with [1) dysbiosis, whereby the gut microbiota becomes less diverse, lacking in healthy butyrate-producing microorganisms and higher in pathogenic bacteria, and [2) loss of epithelial tight junction integrity in the lining of the gut, leading to increased gut permeability and higher metabolic endotoxemia. Animal data suggest that both elements may impact muscle physiology, but human data corroborating the causality of the association between gut microbiota and muscle mass and strength are lacking. Mechanisms wherein the gut microbiota may alter anabolic resistance include an attenuation of gut-derived low-grade inflammation and/or the increased digestibility of protein-containing foods and consequent higher aminoacidemia, both in favour of muscle protein synthesis. This review focuses on the putative links between the gut microbiota and skeletal muscle in the context of sarcopenia. We also address the issue of plant protein digestibility because plant proteins are increasingly important from an environmental sustainability perspective, yet they are less efficient at stimulating muscle protein synthesis than animal proteins.